The Effect of Team Game Tournament to Improve Students’ Speaking Ability at the Second Grade of SMPN 2 Padang - Dinda Legita; Annisha Dyuli Adha; Suparmi Suparmi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The problems of this research were students’ lack of vocabulary, lack of pronunciation, lost confident, a fear of making mistakes, and speaking English is difficult to learn. This research aimed to find out how the TGT method improves students' speaking ability and the significant factors in using the TGT method at SMPN 2 Padang. This research used purposive sampling and VIII.5 as sample in the classroom. This research used qualitative research design and Classroom Action Research approach that consisted 2 cycles, and has four stages, namely; planning, action, observation, and reflection. The instrument of this research was test; pre-test and post-test, observation sheet, and questionnaire. The research results showed a significant increase in students' speaking ability, the improvement of percentage was 18.75% from pre-test to post-test II. The questionnaire revealed that 88.12% of students preferred learning with intrinsic motivation, which showed that the importance of motivation in the learning process.